Cerebral responses to puncturing at different acupoints for treating meal‐related functional dyspepsia. Issue 4 (19th February 2015) - Zeng, F.; Lan, L.; Tang, Y.; Liu, M.; Liu, X.; Song, W.; Li, Y.; Qin, W.; Sun, J.; Yu, S.; Gao, X.; Tian, J.; et al.
Abstract: Background: To investigate the similarities and differences in cerebral responses to puncturing at different acupoints for treating meal‐related functional dyspepsia (FD). Methods: Twenty right‐handed FD patients were enrolled and randomized divided into two groups. Each patient received 20 sessions' electro‐acupuncture treatment. The acupoints used in Group A were four acupoints on the Stomach Meridian, and the acupoints used in Group B were four acupoints on the Gallbladder Meridian. PET‐CT scans were performed before and after acupuncture treatment to record the changes of cerebral glycometabolism. Key Results: After treatment, the dyspepsia symptoms and the quality of life (QOL) of the patients in each group were significantly improved ( p  < 0.05) and there was insignificant difference in efficacy between the two groups ( p  > 0.05). In Group A, deactivation in brainstem, bilateral anterior cingulate cortex (ACC) and cerebellum, left superior medial frontal gyrus, orbital frontal cortex (OFC), and thalamus, etc., and activation in bilateral middle cingulate cortex (MCC), precuneus and lingual gyrus, etc. were observed. In Group B, deactivation in brainstem, bilateral thalamus, putamen, ACC, postterior cingulate cortex, hippocampus and cerebellum, etc., and activation in bilateral MCC, precuneus, left OFC, etc. were observed ( p  < 0.05, Family‐wise error corrected). Conclusions & Inferences: Different acupoints have similar clinical efficacy but relatively different cerebral responses. The influence on the sensory transduction regions (brainstem and thalamus) and visceral modulation regions might be the common mechanism of different acupoints treating for FD, and the modulation on some emotion/cognition‐related areas (e.g., prefrontal cortex) is the potential difference between the different acupoints. Abstract : This study aimed to investigate the similarities and differences in cerebral responses to puncturing at different acupoints for treating meal‐related functional dyspepsia (FD). The results indicated that different acupoints have similar clinical efficacy but relatively different cerebral responses.